Greening human resources management - Iñigo, Eva Maria Magdalena E. (2012)
This paper explores how the human resources managers and the human resources management and development units in selected Philippine companies are involved in the achievement of environmental sustainability goals in their respective companies. Findings showed that HR managers' concepts of environmental sustainability were limited compared to the standard definition of environmental sustainability which covers two interrelated concepts: environmental management and sustainability development. All HR managers however agreed that it was important to mainstream environmental sustainability in all aspects of human resource management and development (HRMD) functions. At the functions' level, HR Managers perceived the roles of HRMD unit in performing internal communication, value formation, providing training expertise, coordinating and mobilizing people to join corporate social responsibility programs. Companies with sustainability framework and corporate values or principles that act as guide in the formulation of environmental sustainability related plans, policies, and programs during strategic planning had more aligned and integrated HR policies, programs and practices and structures. Both the HR managers and environmental advocates enumerated the required HR competencies in the successful planning and implementation of HR policies, programs and practices related to environmental sustainability.
Keywords: Environmental management; Personnel management; Sustainability